The Role of Microorganisms in the Degradation of Pesticides: A Sustainable Approach to Soil Remediation - Varghese, Diya Merlin; Rubiyatno; Lie, Michael; Kristanti, Risky Ayu; Ruti, Annisa Andarini; Nadifah, Gina; Hossain, Ferdaus Mohd Altaf; Jannat, Md Abu Hanifa; Chairattanawat, Chayanee; Direstiyani, Lucky Caesar (Tropical Aquatic and Soil Pollution, 2025)
The widespread use of pesticides in agriculture, aquaculture, and public health has led to severe environmental and public health concerns due to their overapplication and persistence in ecosystems. Pesticide residues accumulate in soil, degrade its fertility, pollute groundwater, and harm non-target organisms, including beneficial insects and aquatic life. This persistent contamination poses a significant threat to biodiversity, food safety, and ecosystem resilience. The aim of this review is to examine microbial bioremediation as a sustainable and effective strategy for remediating pesticide-contaminated soils. The paper evaluates the mechanisms by which microorganisms degrade or transform hazardous pesticide compounds into less toxic or non-toxic forms and assesses the advantages and limitations of bioremediation technologies. Notably, bioremediation is recognized for its environmental compatibility, cost-effectiveness, and potential to restore soil health without undermining agricultural productivity. Recent studies highlight promising microbial strains capable of degrading diverse classes of pesticides under varying environmental conditions. However, challenges remain, including the scalability of microbial technologies, the complexity of mixed-contaminant sites, and the influence of abiotic factors on microbial efficacy. Future research should focus on optimizing microbial consortia, integrating genetic and metabolic engineering approaches, and developing field-scale applications tailored to specific agroecosystems. Advancing these areas will be critical for establishing bioremediation as a central pillar in sustainable pesticide management and environmental restoration strategies.